Nanobody‐aided crystallization of the transcription regulator PaaR2 from Escherichia coli O157:H7. Issue 10 (4th October 2021) - De Bruyn, Pieter; Prolič-Kalinšek, Maruša; Vandervelde, Alexandra; Malfait, Milan; Sterckx, Yann G.-J.; Sobott, Frank; Hadži, San; Pardon, Els; Steyaert, Jan; Loris, Remy
Abstract : Native mass spectrometry was used to screen for nanobodies that allowed crystallization of the transcription regulator PaaR2. Abstract : paaR2 – paaA2 – parE2 is a three‐component toxin–antitoxin module found in prophage CP‐993P of Escherichia coli O157:H7. Transcription regulation of this module occurs via the 123‐amino‐acid regulator PaaR2, which forms a large oligomeric structure. Despite appearing to be well folded, PaaR2 withstands crystallization, as does its N‐terminal DNA‐binding domain. Native mass spectrometry was used to screen for nanobodies that form a unique complex and stabilize the octameric structure of PaaR2. One such nanobody, Nb33, allowed crystallization of the protein. The resulting crystals belong to space group F 432, with unit‐cell parameter a = 317 Å, diffract to 4.0 Å resolution and are likely to contain four PaaR2 monomers and four nanobody monomers in the asymmetric unit. Crystals of two truncates containing the N‐terminal helix–turn–helix domain also interact with Nb33, and the corresponding co‐crystals diffracted to 1.6 and 1.75 Å resolution.